Assessing the Diversity of Endogenous Viruses Throughout Ant Genomes - Flynn, Peter J.; Moreau, Corrie S. (Frontiers in Microbiology, 2019)
Endogenous viral elements (EVEs) can play a significant role in the evolution of their hosts and have been identified in animals, plants, and fungi. Additionally, EVEs potentially provide an important snapshot of the evolutionary frequency of viral infection. The purpose of this study is to take a comparative host-centered approach to EVE discovery in ant genomes to better understand the relationship of EVEs to their ant hosts. Using a comprehensive bioinformatic pipeline, we screened all nineteen published ant genomes for EVEs. Once these EVEs were identified, we assessed their phylogenetic relationships to other closely related exogenous viruses. A diverse group of EVEs derived from ant host genomes were discovered in all screened genomes and in many cases are similar to previously identified exogenous viruses. EVEs similar to ssRNA viral proteins are the most common viral lineage throughout the ant hosts, which is potentially due to more chronic infection or more effective endogenization of certain ssRNA viruses in ants. In addition, both EVEs similar to viral glycoproteins and retrovirus-derived proteins are also abundant throughout ant genomes, suggesting their tendency to endogenize. Several of these newly discovered EVEs are found to be potentially functional within the genome. The discovery and analysis of these EVEs is essential in beginning to understand viral-ant interactions over evolutionary time.